Relationship Between Adenoma Detection Rate and Respective Withdrawal Time in Different Colon Segments: A Retrospective, Single‐Center Study - Xujin Chen; Bingxin Xu; Bingni Wei; Lin Ji; Cheng Yang; Qiang Zhan (JGH Open)
ABSTRACT Background and Aims The 6‐min withdrawal time for colonoscopy is widely considered the standard of care. However, there may not be appropriate if the 6‐min is equally divided into various colon segments. Since the adenoma detection in each colon segment is not the same, there may be differences with the withdrawal time in different colon segments. Our objective was to evaluate the relationships between adenoma detection rate (ADR) and respective withdrawal time in different colon segments. Methods Outpatients, age range 18–75 years, undertaking complete colonoscopy were enrolled in this study from November 2019 to November 2020 in the digestive endoscopy center. The entire colon was divided into four different segments: ascending colon, transverse colon, descending colon and rectosigmoid colon. The respective withdrawal time and ADR in each colon segment were recorded respectively. Results A total of 586 outpatients (279 males, 307 females) enrolled in this study and the general ADR was 38.2%. The positive withdrawal time (adenomas detected) was longer than negative withdrawal time (non‐adenomas detected) (334.04 ± 24.21 s vs. 303.65 ± 5.20 s, t = 1.26, p < 0.001). ADR in ascending colon, transverse colon, descending colon and rectosigmoid colon were respectively 30.5%, 2.9%, 3.1% and 7.5%. While all of their positive withdrawal time were longer than negative withdrawal time (94.34 ± 33.76 s vs. 70.40 ± 41.84 s, t = 3.31, p = 0.001; 85.40 ± 49.76 s vs. 71.66 ± 36.87 s, t = 1.95, p = 0.025; 80.29 ± 39.85 s vs. 69.73 ± 35.96 s, t = 1.40, p = 0.016;100.95 ± 55.92 s vs. 80.96 ± 42.87 s, t = 3.61; p < 0.001, respectively). The withdrawal time threshold in the ascending colon, transverse colon, descending colon, rectosigmoid colon determined by receiver operating characteristic (ROC) curve were 77, 61, 56 and 109 s, respectively. In the ascending colon, ADR was significantly higher (47.0% vs. 33.1%, p < 0.001) when the colonoscopy withdrawal time was ≥ 77 s. When the withdrawal time was ≥ 61 s in the transverse colon (42.7% vs. 32.7%, p = 0.013), ≥ 59 s in the descending colon (42.3% vs. 29.9%, p = 0.004) and ≥ 109 s in rectosigmoid colon (52.2% vs. 33.9%, p < 0.001), ADR was also significantly higher. After adjusting for age, sex and BMI, Logistic regression analysis showed that withdrawal time ≥ 77 s in the ascending colon (OR, 1.796; 95% CI, 1.273–2.532; p < 0.001), ≥ 61 s in the transverse colon (OR, 1.535; 95% CI, 1.094–2.155; p = 0.013), ≥ 56 s in the descending colon (OR, 1.722; 95% CI, 1.193–2.486; p = 0.004) and ≥ 109 s in the rectosigmoid colon (OR, 2.134; 95% CI, 1.446–2.350; p < 0.001) were independent risk factors for the increase of ADR. Conclusions ADR and withdrawal time are all various in individual colon segments. During the operation of colonoscopy, withdrawal time in the ascending colon may be shortened appropriately. The adenomas in the rectosigmoid colon are more likely to be detected and do not take longer withdrawal times. We need to choose the appropriate time according to different colon segments.